Returns to Higher Education in Mexico: A Cross-Sectional Analysis, 2010–2024 - Janeth Yadira Rodríguez Galván; Juan Francisco Islas Aguirre (Economies)
This study evaluates the socioeconomic effects of educational policies implemented between 2010 and 2024 within the context of the Fourth Industrial Revolution, focusing on the labor demand for professionals with advanced competencies. Using a quantitative analysis based on microdata from the National Survey of Occupation and Employment (ENOE) for 2010–2024, an econometric model is employed to estimate the returns to education and work experience and analyze gender wage gaps and the urban–rural distribution. The findings reveal a 46.3% increase in the labor market participation of individuals with higher education and a rise in wage disparities, particularly in the Information and Communication Technology sector. Limited to ENOE data in Mexico, this research adds value by identifying the mismatch between educational supply and emerging labor market demands. The conclusions suggest adjusting educational policies to reduce gender gaps and better equip graduates to meet current challenges.